EVERY PERSON SHALL BE ENTITLED TO FREEDOM OF EXPRESSION: REDEFINING PRESS FREEDOMS IN THE LIGHT OF SECTION 39 OF THE CONSTITUION OF THE FEDERAL REPUBLIC OF NIGERIA (AS AMENDED) - Victor AGANBI, (IJRDO - Journal of Social Science and Humanities Research, 2020)
This paper concerns itself with the argument that our primary understanding of press freedoms may not be the true representation of the intention of the lawmakers and that due to several factors our primary definition of a journalist is due an update. By using a doctrinal method of research, the paper discussed press freedoms in light of Section 39 of The Constitution of the Federal Republic of Nigeria (as amended). This paper discussed the provisions of the Nigerian Constitution which serve as the legal framework for the journalism profession in Nigeria. The paper highlights that because of the shortcomings of these sections, they do not contain the required legal framework for press freedoms, the journalism profession and freedom of information in Nigeria. The paper discussed the meaning of the term journalist in today’s digital age and found that the internet has challenged many of the definitions of what a journalist is and thus who should enjoy press freedoms. This research adopts a non-doctrinal, multi-disciplinary methods.